Chemical variability between different organs of the medicinal plant casearia sylvestris - Carvalho, Flavio Alexandre [UNESP]; Aguilar, Polyanna Pereira [UNESP]; Oda, Fernando Bombarda [UNESP]; Uchina, Helena Sayuri [UNESP]; Tininis, Aristeu Gomes; Crevelin, Eduardo José; Crotti, Antônio Eduardo Miller; Dos Santos, André Gonzaga [UNESP] (My University, 2018)
The phytochemical profile of essential oils and extracts from Casearia sylvestris leaves, flowers and fruits have been investigated here. Leaf and flower extracts were prepared by sonication and analyzed by thin-layer chromatography and high-performance liquid chromatography. The phenolic content was determined by ultraviolet spectrophotometry. Leaves, flowers, and fruits essential oils were extracted by hydrodistillation. The highest extracts yields were 20.3% (leaves) and 23.4% (flowers) with ethanol 70%. Essential oil extraction yields were 0.3% (leaves) and 0.1% (flowers and fruits). Bicyclogermacrene was the major component in all essential oil. Thin-layer chromatography suggests a chemical profile similar for leaves and flowers. The leaves and flowers phenolic contents were similar (14.0 and 15.0%, respectively). Chromatographic analyses indicated the predominance of casearin clerodane diterpenes in leaves (λmax 232-235), whereas in flowers diterpenes with a different standard diene in side-chain C13(16) and C14 (λmax 223-229). The different phytochemical profile of C. sylvestris flowers as compared to the leaves could be explored by the search for new bioactive components. This is the first report on the fruit and flower C. sylvestris essential oil composition. These data could be used as quality control of herbal medicine derived from C. sylvestris leaves.
Variabilidade química entre diferentes órgãos da planta medicinal casearia sylvestris
Keywords: Bicyclogermacrene; Clerodane Diterpenes; Essential Oil; Quality control